Preserving Protest: Collecting Contemporaneously - Franzus, Aline (Satura, 2022)
In the social media age we find ourselves in, great ambivalences of relevance reveal themselves daily: one moment our timelines are flooded with impressions of protest, while the next they are filled with plant care videos, recipe posts, or any other content an algorithm has neatly selected for us. In recent years, there has been a surge in protest marches and demonstrations globally1, voicing demands and making public “memories excluded from national history books and mainstream media audiences” (Doerr 206). During a time when many people take to the streets for reasons as varied as German weather in April, the images of protest seem ubiquitous, yet fleeting. They do not stay – at least not on our social media timelines.